Pregnancy-related lumbopelvic pain in early postpartum period and risk factorr - Terzi, Hasan; Terzi, Rabia; Altınbilek, Turgay (International Journal of Research in Medical Sciences, 2017)
Background: Pregnancy-related lumbopelvic pain is known as lower back and pelvic girdle pain of unclear etiology, which affects almost half of pregnant women, often starts at 18 weeks and decreases at 6 months postpartum. The purpose of this study is to identify the risk factors in patients with pregnancy-related lumbopelvic pain in early postpartum period and determine the factors associated with pain in patients suffering from lumbopelvic pain at 1 month postpartum. Methods: 339 women of 18-40 years of age who were in the 1st month of postpartum period were included in the study. Socio-demographic data, gynecological history and method of delivery were recorded for all subjects. All subjects were evaluated for pregnancy-related lumbopelvic pain. The Oswestry disability index was used for functional evaluation and the Beck depression inventory was used for assessment of depression. Results: 114 (33.6%) patients had a history of pregnancy-related lumbopelvic pain. 59 (18.9%) patients had ongoing pain at 1 month postpartum. When patients were divided into two groups, consisting of women with and without lumbopelvic pain at 1 month postpartum, no statistical difference was observed between two groups in terms of age, parity, employment status, smoking status, depression score, method of delivery, type of anesthesia, and emergency or elective cesarean section. When the risk factors affecting postpartum lumbopelvic pain were evaluated by using the Stepwise Logistic regression analysis, weight gain during pregnancy, body mass index and presence of lumbopelvic pain during previous pregnancy were found to be independent risk factors (p<0.05). Conclusion: Pregnancy-related lumbopelvic pain is a significant cause of disability that affects many pregnant women. Control of weight gain during pregnancy could be important in avoiding the development of lumbopelvic pain. In patients experiencing lumbopelvic pain in previous pregnancies, necessary measures should be taken against development of lumbopelvic pain during a new pregnancy.